Antibacterial and phenolic content of propolis produced by two Malaysian stingless bees, Heterotrigona itama and Geniotrigona thoracica - Abd Jamil, Zakaria; Khamsah Suryati, Mohd; Zhari, Ismail (International Journal of Pharmacognosy and Phytochemical Research, 2016)
Propolis is a sticky material collected by the bees to protect their hive. It has been used for medicinal purposes since ancient time. The methanol extract of Malaysian propolis produced by two commonly found stingless bees, Heterotrigona itama (MHI) and Geniotrigona thoracica (MGT) inhibited the growth of Staphylococcus aureus better than Gram-negative (Escherichia coli and Salmonella typhi) bacteria. However, the minimum inhibitory concentration (MIC) values showed the most effective propolis was MHI (5 mg/mL) for Gram-positive and 10 mg/mL for Gram-negative compared to MGT has showed less activity against all tested bacteria. Chemical fingerprint was derived from thin layer chromatography analysis. Both extract displayed a characteristic profile and vary from each other. Analysis of Fourier transform Infrared (FT-IR) spectra of both extract tested show similar IR spectral profiles but from the intensities of both extract have significant differences. The results indicate that the differences are caused by group of phenolic and flavonoid. Total phenolic and flavonoid content of MHI of 56.9 ± 0.12 ug/mL and 163.9 ± 0.10 μg/mL, respectively was higher than MGT of 29.1 ± 0.10 ug/mL and 61.5 ± 0.15 μg/mL, respectively. These results showed that the antibacterial activity and chemical analysis of propolis do vary according to its species of stingless bees.